Visual attention in mixed-gender groups - Amon, Mary Jean (Frontiers in Psychology, 2015)
A basic principle of objectification theory is that a mere glance from a stranger represents the potential to be sexualized, triggering women to take on the perspective of others and become vigilant to their appearance. However, research has yet to document gendered gaze patterns in social groups. The present study examined visual attention in groups of varying gender composition to understand how gender and minority status influence gaze behavior. One hundred undergraduates enrolled in psychology courses were photographed, and an additional 76 participants viewed groupings of these photographs while their point of gaze was recorded using a remote eye-tracking device. Participants were not told that their gaze was being recorded. Women were viewed more frequently and for longer periods of time than men in mixed-gender groups. Women were also more likely to be looked at first and last by observers. Men spent more time attending to pictures of women when fewer women were in the group. The opposite effect was found for pictures of men, such that male pictures were viewed less when fewer pictures of men were in the group. Female observers spent more time looking at men compared to male observers, and male observers spent more time looking at women than female observers, though both female and male observers looked at women more than men overall. Consistent with objectification theory, women’s appearance garners more attention and interest in mixed-gender social groups.